How multimedia works - Holsinger, Erik.; Berger, Nevin (Emeryville, California : Ziff-Davis Press, 1994)
Stunning graphics and lucid text make this a guide for everyone who is curious about multimedia and how it affects our lives, including multimedia that surrounds us, creating a multimedia project, and technologies used for such special effects as 3D animation. Original. (Beginner).
Inside a multimedia title -- Multimedia system software and hardware -- Understanding digital video -- Understanding digital audio -- Alternate distribution platforms -- CD-ROMs and laser discs -- Interactive entertainment.
Includes index.
Keywords: MULTIMEDIA SYSTEMS